Green Infrastructure Planning Principles - Monteiro, Renato (2022)
Acknowledgments: The authors acknowledge and thank the support given by the Portuguese Foundation for Science and Technology (FCT) to MARE through the strategic projects UIDB/04292/2020 and UIDP/04292/2020, and CENSE through the strategic project UIDB/04085/2020. Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.